The Biological Basis for Cardiac Repair After Myocardial Infarction: From Inflammation to Fibrosis. Issue 1 (24th June 2016) - Prabhu, Sumanth D.; Frangogiannis, Nikolaos G.
Abstract : In adult mammals, massive sudden loss of cardiomyocytes after infarction overwhelms the limited regenerative capacity of the myocardium, resulting in the formation of a collagen-based scar. Necrotic cells release danger signals, activating innate immune pathways and triggering an intense inflammatory response. Stimulation of toll-like receptor signaling and complement activation induces expression of proinflammatory cytokines (such as interleukin-1 and tumor necrosis factor-α) and chemokines (such as monocyte chemoattractant protein-1/ chemokine (C-C motif) ligand 2 [CCL2]). Inflammatory signals promote adhesive interactions between leukocytes and endothelial cells, leading to extravasation of neutrophils and monocytes. As infiltrating leukocytes clear the infarct from dead cells, mediators repressing inflammation are released, and anti-inflammatory mononuclear cell subsets predominate. Suppression of the inflammatory response is associated with activation of reparative cells. Fibroblasts proliferate, undergo myofibroblast transdifferentiation, and deposit large amounts of extracellular matrix proteins maintaining the structural integrity of the infarcted ventricle. The renin–angiotensin–aldosterone system and members of the transforming growth factor-β family play an important role in activation of infarct myofibroblasts. Maturation of the scar follows, as a network of cross-linked collagenous matrix is formed and granulation tissue cells become apoptotic. This review discusses the cellular effectors and molecular signals regulating the inflammatory and reparative response after myocardial infarction. Dysregulation of immune pathways, impaired suppression of postinfarction inflammation, perturbed spatial containment of the inflammatory response, and overactive fibrosis may cause adverse remodeling in patients with infarction contributing to the pathogenesis of heart failure. Therapeutic modulation of the inflammatory and reparative response may hold promise for the prevention of postinfarction heart failure.